Application of six sigma in the case study of a phosphate mine - Araxá-MG (Research, Society and Development, 2020)
This work aims to present the applicability of the Six Sigma methodology to optimize operations management activities at a phosphate mine in the municipality of Araxá, Minas Gerais, and thus to improve the block model. For this, the DMAIC - Define, Measure, Analyze, Improve and Control model was used. Initially defined the problem, then the perspective of mine geology research and in the later stages, continuous improvement tools were used, such as: process map, pareto chart, cause and effect diagram including KPI's - Key Performance Indicator, GUT(Gravity, Urgency and Tendency) matrix and control chart, made using the MiniTab software. The results present sampling as the main indicator and develops action plans to complement the basic work. Therefore, it is possible to understand the importance of the Six Sigma methodology applied in mine geology and its representativeness in the optimization of operations, using continuous improvement techniques.